Surfactant free novel one-minute microwave synthesis, characterization and cell toxicity study of mesoporous strontium hydroxyapatite nanorods. Issue 97 (4th October 2016) - Agrawal, Shital; Kelkar, Madhura; De, Abhijit; Kulkarni, A. R.; Gandhi, M. N.
Abstract : Synthesis of mesoporous strontium hydroxyapatite (SrHAp) nanorods was carried out in microwave without using any capping agent or surfactant. Abstract : Synthesis of mesoporous strontium hydroxyapatite (SrHAp) nanorods was carried out in a microwave without using any capping agent or surfactant. Nanorod formation was successfully achieved even at temperatures as low as 140 °C with 1 min hold time. Field emission gun transmission electron microscopy (FEG-TEM) and scanning electron microscopy (SEM) indicated monodisperse, uniform and mesoporous nanorods with average dimensions: length 98.87 nm, width 18.87 nm and pore size 2–5 nm. XRD analysis showed that the sample consisted of a single phase made up of highly crystalline nanorods with a P 63 / m symmetry group. Fourier transform infrared spectroscopy (FTIR) and energy dispersive X-ray spectroscopy (EDX) confirmed that the chemical and elemental composition was that of strontium hydroxyapatite. Surface area and pore volume were calculated from nitrogen adsorption and desorption isotherms as 40.13 m 2 g −1 and 0.45 cm 3 g −1, respectively. The material was found to be non toxic to NIH3T3, MCF-7 and Zr-75 cells even at concentrations of 0.25 mg ml −1, and after 24 and 48 hours of incubation. Thus, owing to its high surface area, pore volume and good cell viability, this material showed good potential for anticancer and other drug delivery applications.